Nitrous oxide‐induced myeloneuropathy. (6th September 2021) - Swart, Grace; Blair, Christopher; Lu, Zhong; Yogendran, Solomon; Offord, Joanna; Sutherland, Emily; Barnes, Stephanie; Palavra, Natalie; Cremer, Phillip; Bolitho, Samuel; Michael Halmagyi, Gabor
Abstract: Background and purpose: Nitrous oxide misuse is a recognized issue worldwide. Prolonged misuse inactivates vitamin B12, causing a myeloneuropathy. Methods: Twenty patients presenting between 2016 and 2020 to tertiary hospitals in Sydney with myeloneuropathy due to nitrous oxide misuse were reviewed. Results: The average age was 24 years, and mean canister consumption was 148 per day for 9 months. At presentation, paresthesias and gait unsteadiness were common, and seven patients were bedbound. Mean serum B12 was normal (258 pmol/L, normal range [NR] = 140–750) as was active B12 (87 pmol/L, normal > 35). In contrast, mean serum homocysteine was high (51 μmol/L, NR = 5–15). Spinal magnetic resonance imaging (MRI) showed characteristic dorsal column T2 hyperintensities in all 20 patients. Nerve conduction studies showed a predominantly axonal sensorimotor neuropathy ( n = 5). Patients were treated with intramuscular vitamin B12, with variable functional recovery. Three of the seven patients who were bedbound at presentation were able to walk again with an aid at discharge. Of eight patients with follow‐up data, most had persistent paresthesias and/or sensory ataxia. Mobility scores at admission and discharge were not significantly correlated with the serum total and active B12 levels or cumulative nitrous oxide use. There were no significant trends between serum active B12 level and cumulative nitrous oxide use (Spearman rho = −0.331, p = 0.195). Conclusions: Nitrous oxide misuse can cause a severe but potentially reversible subacute myeloneuropathy. Serum and active B12 can be normal, while elevated homocysteine and dorsal column high T2 signal on MRI strongly suggest the diagnosis. Neurological deficits can improve with abstinence and B12 supplementation, even in the most severely affected patients. Abstract : This study reviewed 20 patients presenting between 2016 and 2020 to tertiary hospitals in Australia with myeloneuropathy due to heavy nitrous oxide misuse. Mean serum and active B12 were normal; in contrast, mean serum homocysteine was high (51 μmol/L, normal range = 5–15). Spinal magnetic resonance imaging (MRI; n = 20) showed dorsal column T2 hyperintensities. All patients were treated with intramuscular vitamin B12, with variable functional recovery; three of seven patients who were bedbound at presentation walked with an aid at discharge. Nitrous oxide misuse can cause a severe but potentially reversible subacute myeloneuropathy. Elevated homocysteine and dorsal column high T2 signal on MRI strongly suggest the diagnosis.